The Neumann Problem of Complex Special Lagrangian Equations with Supercritical Phase (Analysis in Theory and Applications, 2019)
Inspired by the Neumann problem of real special Lagrangian equations with supercritical phase, we consider the Neumann problem of complex special Lagrangian equations with supercritical phase in this paper, and establish the global $C^2$ estimates and the existence theorem by the method of continuity.
Keywords: Special Lagrangian equation; Neumann problem; supercritical phase.